From Controversy to Cohesion: Managing Religious Tension in Malaysia through Socioreligious Harmony Frameworks - Ahmad Yusoff, Atifah; Ghazali, Alwani; Mohd Khambali @ Hambali , Khadijah; Waipin, Noorafifah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
In 1938, Samuel P. Huntington notoriously argued that “the great divisions among humankind and the dominating source of conflict will be cultural,” a thesis that has since fuelled misconceptions about the inherent incompatibility of civilizations based on religious, ethnic, and racial differences. This perspective has particularly negatively impacted views of Islam when he added that “the crescent-shaped Islamic bloc, from the bulge of Africa to central Asia, has bloody borders.” Using a qualitative, library-based research approach, this article explores the contemporary challenges of religious tensions in Malaysia. It investigates whether meaningful interreligious coexistence is viable in a multi-religious country. These challenges, including prejudice and stereotyping, can be addressed through a comprehensive understanding of socio-religious harmony in Islamic perspectives that can be formulated by engaging with the commonalities perspective of religion, the principle of human brotherhood, the value of mutual tolerance (tasamuh), the role of dialogue and peaceful coexistence (fiqh al-ta‘ayush). Practical methods for implementing these values include interfaith education, community engagement, inclusive policymaking, and dialogue platforms that resonate with local cultural contexts. Together, these elements contribute to an integrated framework of harmonious socio-religious relations.